Poems on Bishops by Gregory of Nazianzus and Ephrem the Syrian: Literary Comparison and Translation - Colpani, Giovanni (Millennium-Studien / Millennium Studies, 2025)
This study is the first extensive comparison of poems by Gregory of Nazianzus and Ephrem the Syrian focused on their form, imagery and literary strategies. The poems selected have historical significance thanks to their common theme: Gregory and Ephrem are the first to write verse on bishops in Greek and Syriac respectively. A new English translation of the texts is appended to the study.